2021
DOI: 10.7181/acfs.2021.00241
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of facial asymmetry after zygomaticomaxillary complex fracture reduction: a retrospective analysis of 101 East Asian patients

Abstract: Background:The zygomaticomaxillary complex (ZMC) has a protruded, convex shape and plays a vital role in determining the contour by affecting the width of the middle face. This study aimed to evaluate the efficiency of ZMC fracture reduction and explore detailed directions for outcome improvement. Methods: We conducted a retrospective study of patients diagnosed with unilateral ZMC fracture who underwent ZMC reduction surgery at a single hospital between January 2015 and May 2020. The primary outcome variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…This knowledge can be especially important in patients with facial trauma, particularly fractures of the buccal surface of the zygomatic bone shaft, as the zygomatic bone is the most prominent part of the facial skeleton [19,31]. After zygomaticomaxillary complex fracture all patients have performed the 3-dimentional analysis of the degree of recovery of malar asymmetry [3]. This 3D image is essential before reconstruction operation and the DZ could be seen in the frontal view, which could be misunderstanding.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge can be especially important in patients with facial trauma, particularly fractures of the buccal surface of the zygomatic bone shaft, as the zygomatic bone is the most prominent part of the facial skeleton [19,31]. After zygomaticomaxillary complex fracture all patients have performed the 3-dimentional analysis of the degree of recovery of malar asymmetry [3]. This 3D image is essential before reconstruction operation and the DZ could be seen in the frontal view, which could be misunderstanding.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that intraoral incisions and small local incisions can meet the surgical requirements. 32,33 However, bilateral ZMC fractures are usually accompanied by full-face fractures, which are often complicated with comminuted fractures. For the ZMC fracture with obvious displacement and comminuted fractures, the fracture site cannot be fully exposed at the small incision, and the fracture site can be maximally exposed at the coronal incision combined with other incisions, which is one of the foundations of accurate reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that intraoral incisions and small local incisions can meet the surgical requirements 32,33 . However, bilateral ZMC fractures are usually accompanied by full-face fractures, which are often complicated with comminuted fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The zygomatic arch is a cylindrical, thin, and long bridge-like structure that is structurally vulnerable to local trauma; fractures commonly result from both high- and low-velocity forces [ 2 ]. Zygomatic arch fractures often occur as part of zygomaticomaxillary complex fractures, which account for approximately 25% of all facial bone fractures, whereas isolated zygomatic arch fractures comprise 10% of all zygoma fractures and 5% of all facial fractures [ 3 – 5 ]. Zygomatic arch fractures cause esthetic problems due to the facial asymmetry resulting from lateral facial flattening and depression in the affected area and functional problems due to coronoid impingement [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%